2020
DOI: 10.3390/ma13092136
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Restrained Condition on Mechanical Properties, Frost Resistance, and Carbonation Resistance of Expansive Concrete

Abstract: This paper presents the results of an experimental investigation of the effect of the restrained condition on the mechanical properties, frost resistance, and carbonation resistance of expansive concrete with different water–binder ratios. In this study, length change ratio test, expansion strain test, compressive strength test, mercury intrusion porosimetry test, underwater weighing test, freezing–thawing test, and accelerated carbonation test were performed to evaluate the mechanical properties, pore size di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Still, whether the influence is positive or negative, the literature shows that it is slight and insignificant. 57,58,81,82 Regardless, using superplasticizer is a requirement, especially with high strength concrete when the water/ cement ratio is low. There are a number of superplasticizer available; however, Zdanowicz 23 has shown that polycarboxylate ether (PCE) superplasticizers are more effective in promoting expansion than other types.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…Still, whether the influence is positive or negative, the literature shows that it is slight and insignificant. 57,58,81,82 Regardless, using superplasticizer is a requirement, especially with high strength concrete when the water/ cement ratio is low. There are a number of superplasticizer available; however, Zdanowicz 23 has shown that polycarboxylate ether (PCE) superplasticizers are more effective in promoting expansion than other types.…”
Section: F I G U R Ementioning
confidence: 99%
“…There are conflicting reports regarding the influence of CSA on the workability of fresh concrete. Still, whether the influence is positive or negative, the literature shows that it is slight and insignificant 57,58,81,82 . Regardless, using superplasticizer is a requirement, especially with high strength concrete when the water/cement ratio is low.…”
Section: Mixture Component Of Expansive Concretementioning
confidence: 99%
“…Expansive concretes made of expansive cements are characterized by lower total porosity and thus lower permeability of composite, as well as better frost resistance and higher strength compared to concretes from non-expansive cements [ 5 ]. The disadvantage of sulfate-containing expansive cements is the possibility of the formation of ettringite after the cement sets, which leads to cracking of the cement matrix.…”
Section: Introductionmentioning
confidence: 99%